Medullary kappa-opioid receptor neurons inhibit pain and itch through a descending circuit - Nguyen, Eileen; Smith, Kelly M; Cramer, Nathan; Holland, Ruby A; Bleimeister, Isabel H; Flores-Felix, Krystal; Silberberg, Hanna; Keller, Asaf; Le Pichon, Claire E; Ross, Sarah E (Brain (London, England : 1878), 2022)
In perilous and stressful situations, the ability to suppress pain can be critical for survival. The rostral ventromedial medulla contains neurons that robustly inhibit nocioception at the level of the spinal cord through a top-down modulatory pathway. Although much is known about the role of the rostral ventromedial medulla in the inhibition of pain, the precise ability to directly manipulate pain-inhibitory neurons in the rostral ventromedial medulla has never been achieved. We now expose a cellular circuit that inhibits nocioception and itch in mice. Through a combination of molecular, tracing and behavioural approaches, we found that rostral ventromedial medulla neurons containing the kappa-opioid receptor inhibit itch and nocioception. With chemogenetic inhibition, we uncovered that these neurons are required for stress-induced analgesia. Using intersectional chemogenetic and pharmacological approaches, we determined that rostral ventromedial medulla kappa-opioid receptor neurons inhibit nocioception and itch through a descending circuit. Lastly, we identified a dynorphinergic pathway arising from the periaqueductal grey that modulates nociception within the rostral ventromedial medulla. These discoveries highlight a distinct population of rostral ventromedial medulla neurons capable of broadly and robustly inhibiting itch and nocioception.